Cranial suture headache: An extracranial head pain syndrome originating in the cranial sutures of the skull. (16th August 2021) - Rozen, Todd D
Objective: To define a new type of head pain syndrome termed "cranial suture headache" which is a localized headache originating along the cranial suture lines of the skull. Background: Well localized headaches maybe extracranial in origin. As trigeminal nociceptors are localized within the cranial sutures of the skull, these fibrous joints maybe the source of head pain for some patients. Methods: Case series. To diagnose cranial suture headache, the patient's pain had to be localized to the skull and elicited/mimicked by mild to moderate palpation over one or more distinct cranial suture lines. Results: Ten cases are presented. Most of the patients were women (9/10). The headache started daily from onset in all cases. Range of age of headache onset was 32–64 years. Headache was one sided, unless confined to the midline and typically lacked any migrainous and/or cranial autonomic symptoms. Most cranial suture headaches localized to either the sagittal, coronal or squamosal suture lines. Headache duration prior to diagnosis was on average 8.5 years. Triggering events: three began immediately after head trauma, two had very remote head trauma, one was post infectious, one was post craniotomy, while three patients had no known triggering event. All patients were treatment refractory failing at least three preventive medications. All improved with localized anesthetic injection to the suture line(s) and/or onabotulinum toxin A injection only to the cranial sutures. Discussion: Without the recognition of cranial suture-based pain, patients may have unremitting headaches that can last years to decades. The observation that "cranial suture" headache improves with localized treatment only to the cranial sutures would seem to suggest the extracranial origin of the pain.